INCREASING LOCAL FRUITS COMPETITIVENESS IN ENTERING THE TOURISM MARKET IN BALI - Wirawan, I Gede Putu; Srie Marhaeni Julyasih, Ketut; Adiartayasa, Wayan; Wijaya, I Nyoman; Anom, I Putu (International Journal of Biosciences and Biotechnology; Vol 2 No 1 (2014), 2014)
The study focused on improving the fruit quality supported by handling of the cultivation, harvest and post-??harve st handling such as fruit packing, transportation, storage, and others, as well as marketing strategiesand regulations that are ne eded locally, so local Bali fruits can compete better in the Bali tourism market.The purposes of this study were to find some problems face by the local fruits to e nter the tourism marke t inBali. The local fruits studied were citrus, salacca, mangoes, mangosteen, banana, and papaya. This study wasthrough multiple surveys such as, inte rviews with farme rs, whole salers, fruit suppliers, and the manage rsof the hote ls and restaurants. The results of this study found some local fruits have e nte red the tourismmarket in Bali, in addition, local people in Bali te nd to consume the imported fruits for some culturalceremony, events and others.The results of this study showthat the main problems in the local fruits suchas citrus and banana were harvesting, packaging, storage, and transportation. The laboratory studies foundthat some microbes and inse cts infe cted local fruits due to the lackof handling such as packaging, storage,and transportation. The findings of this study was local fruits such as orange s and bananas face manyobstacles ranging from harvest, post-??harvest management, transportation, and the marketing strategies.Many problem has found on bananas such as damaged on storage, as well as citrus fruits. Improvements tothe appearance of the fruit has been tried to do by the application of emulsion of he rbal oils, oleic acid, wax,twee n, and the results showe d the fruits still in a fre sh condition afte r four weeks of treatme nt while theuntre ated fruits were rotten due tothe infe ction of microbes. The blackspots of insects ormicrobes infectionson the treated fruits can be eliminated as well. Some inse cts and microbial attacks were found that leads tofruit rot which can essentially be removed by tre atment with antimicrobial tre atment. This research tries tochart the effects on the competitiveness of local fruits, such as continuity of production, standardization andregulation which could be developed at the local level in the village community.
Keywords: Local fruits, competitiveness, emulsion, regulation